Targeted nutritional intervention attenuates experimental lung cancer cachexia - Wouter R. P. H. van deWorp; Jan Theys; Cecile J. A. Wolfs; Frank Verhaegen; Annemie M. W. J. Schols; Ardy vanHelvoort; Ramon C. J. Langen (Wiley, 2024)
Abstract Background Cachexia, a syndrome with high prevalence in non‐small cell lung cancer patients, impairs quality of life and reduces tolerance and responsiveness to cancer therapy resulting in decreased survival. Optimal nutritional care is pivotal in the treatment of cachexia and a recommended cornerstone of multimodal therapy. Here, we investigated the therapeutic effect of an intervention diet consisting of a specific combination of high protein, leucine, fish oil, vitamin D, galacto‐oligosaccharides, and fructo‐oligosaccharides on the development and progression of cachexia in an orthotopic lung cancer mouse model. Methods Eleven‐week‐old male 129S2/Sv mice were orthotopically implanted with 344P lung epithelial tumour cells or vehicle (control). Seven days post‐implantation tumour‐bearing (TB) mice were allocated to either intervention‐ or isocaloric control diet. Cachexia was defined as 5 days of consecutive body weight loss, after which mice were euthanized for tissue analyses. Results TB mice developed cachexia accompanied by significant loss of skeletal muscle mass and epididymal fat mass compared with sham operated mice. The cachectic endpoint was significantly delayed (46.0 ± 15.2 vs. 34.7 ± 11.4 days), and the amount (−1.57 ± 0.62 vs. −2.13 ± 0.57 g) and progression (−0.26 ± 0.14 vs. −0.39 ± 0.11 g/day) of body weight loss were significantly reduced by the intervention compared with control diet. Moreover, systemic inflammation (pentraxin‐2 plasma levels) and alterations in molecular markers for proteolysis and protein synthesis, indicative of muscle atrophy signalling in TB‐mice, were suppressed in skeletal muscle by the intervention diet. Conclusions Together, these data demonstrate the potential of this multinutrient intervention, targeting multiple components of cachexia, as integral part of lung cancer management.